Fluktuasi parameter kualitas air dan perkembangan flok pada budidaya ikan Nila (Oreochromis niloticus) dengan sistem bioflok di BPBAT Talelu - Franklin R. Safsafubun; Suzanne L. Undap; Indra R.N. Salindeho; Novie P.L. Pangemanan; Juliaan Ch. Watung; Henneke Pangkey (e-Journal BUDIDAYA PERAIRAN, 2023)
This study aims to determine fluctuations in water quality parameters and flock development in tilapia (Oreochromis niloticus) aquaculture using the biofloc system. The water quality parameters studied were temperature, DO (Dissolved Oxygen), pH, ammonia (NH4), nitrite (NO2), and nitrate (NO3). The research was carried out at the Freshwater Aquaculture Fisheries Center (BPBAT) Tatelu, from May 2023 to June 2023, using the case study method. The average temperature during the study was 27.2oC, DO (5.05 mg/L) and pH (5.40). The average NH4 value was 0.58 mg/L. The results of this study indicated that ammonia began to increase from the first day and reached a peak on day 5 with a value of 0.77 mg/L. The average NO2 value was 1.12 mg/L, The results of this study indicated that the increase in NO2 occurred rapidly from day 5 and reached a peak on day 27 with a value of 1.92 mg/L, then began to decline. The average NO3 value was 25.21 mg/L, the NO3 value increased on the 12th day to a value of 35.1 mg/L, and this value began to stabilize even though there was a little pressure. The highest floc density was on the 34th day with a value of 34 ml/L, the lowest was on the 11th day with a value of 4 ml/L and the average floc density was 23 ml/L. Tilapia culture in the biofloc system had an absolute growth of 57.11 grams, a specific growth ratio of 1.5%, feed conversion (FCR) of 1.2, and survival of 97%. Keywords: Fish cultivation, Oreochromis niloticus, biofloc system